Development of spiral square coils for magnetic labelling detection in microfluidic systems - Feddag, Abdelhadi; Mekkakia-Maaza, Nasr-Eddine; Lakhdari, Abdelghani (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Due to the development of microfluidic systems biomedical microelectromechanical systems (BioMEMS) for magnetic labelling detection by magnetic microbeads circling in microfluidic channels, we used the magnetic field created by microcoils. The magnetic field associated with the electric current, but with negatively affects if its value increases too much. Handling bio-species in the microfluidic chip requires that the temperature maintained to keep the cells to prevent their destruction. In this paper we have described the spiral square coil design of different structures to produce an effective magnetic flux density. The simulation of the magnetic flux density is carried out with the help of the COMSOL software. We have presented an optimization of the geometric parameters of the microcoil for a better performance and a miniaturization of the structure with copper wire section S=25 µm2 and inter-wire space a=5 µm. We have also developed this microcoil by adding a ferromagnetic core to the inner center, the results obtained in this work shown that the magnetic flux density increases around 1.07 times in Bx and 1.45 times in Bz. This new approach in designing a microcoil allows to obtaining a fast trapping of the microbeads and a highly sensitive biological element detection and avoiding increase heat ratio in microfluidic systems.